Main factors in the continuity of family business - Rivero Ponce de León, Eduardo Rubén (2019)
Given the importance of family businesses in the economy of different countries, and the scope of  these only 10% to the third generation, it is necessary to identify the main factors that affect the continuity of this type of companies. For this, it is necessary to review the literature in this regard, in order to identify the main factors that should be considered in the continuity of family businesses. In this respect the main topics proposed by leading researchers at an international level have been analyzed, and applied in the case of family businesses in Peru. It is a descriptive investigation based on documentary research. At the final part of the thesis, the main factors that should be considered in the continuity of family businesses will be identified.